2014
DOI: 10.1371/journal.pone.0091718
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Uncertainty: Woodpecker Finches (Cactospiza pallida) from an Unpredictable Habitat Are More Flexible than Birds from a Stable Habitat

Abstract: Behavioural flexibility is thought to be a major factor in evolution. It may facilitate the discovery and exploitation of new resources, which in turn may expose populations to novel selective forces and facilitate adaptive radiation. Darwin's finches are a textbook example of adaptive radiation. They are fast learners and show a range of unusual foraging techniques, probably as a result of their flexibility. In this study we aimed to test whether variability of the environment is correlated with flexibility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 38 publications
(54 reference statements)
0
43
0
Order By: Relevance
“…61 ). Comparative studies have shown that species facing high variability in food supply 65 , complex social environments 30 or variation in foraging strategies 66 show higher performance in reversal learning than similar species living in more stable and predictable environments. Measuring inter-individual differences in reversal learning in the wild will enable us to better understand how natural selection operates on related cognitive abilities in species faced with rapidly changing environments 1 , 2 .…”
Section: Discussionmentioning
confidence: 99%
“…61 ). Comparative studies have shown that species facing high variability in food supply 65 , complex social environments 30 or variation in foraging strategies 66 show higher performance in reversal learning than similar species living in more stable and predictable environments. Measuring inter-individual differences in reversal learning in the wild will enable us to better understand how natural selection operates on related cognitive abilities in species faced with rapidly changing environments 1 , 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, highly social species are expected to express more flexible behaviour than less social species (Bond, Kamil, & Balda, ; Easton, ). Also variation in biotic and abiotic ecological factors, including food abundance and predation risk, can favour the evolution of greater behavioural flexibility, where more variable environments are expected to favour greater flexibility than stable environments (Day, Coe, Kendal, & Laland, ; Jones, ; Sol, Griffin, Bartomeus, & Boyce, ; Tebbich, Stankewitz, & Teschke, ; Tebbich & Teschke, ; Tomasello & Call, ). Learning is an important form of behavioural flexibility enabling animals to adapt to local environmental conditions and to cope with short‐term environmental fluctuations (Mery & Burns, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the current study further contributes to the growing number of studies comparing cognitive performance among populations inhabiting different environments to understand the evolution of cognitive mechanisms (e.g. Audet, Ducatez, & Lefebvre, 2015; Bond, Kamil, & Balda, 2007; Pravosudov & Clayton, 2002; Tebbich & Teschke, 2014). Our results are consistent with the hypothesis that ecology can drive adaptive cognitive processes, such that the local environment leads populations to more quickly associate specific cues with certain behavioural outcomes.…”
Section: Discussionmentioning
confidence: 90%